The heart of the ageing endurance athlete: the role of chronic coronary stress - Parry-Williams, G.; Gati, S.; Sharma, S. (European Heart Journal, 2021)
Moderate physical exercise is associated with an irrefutable reduction in cardiac morbidity and mortality. The current guidelines recommend at least 150 min of moderate exercise or 75 min of vigorous exercise per week. Endurance athletes perform exercise at a level that is 10- to 20-fold greater than these recommendations. These athletes reveal several structural and functional cardiac adaptations including increased cardiac size, enhanced ventricular filling, and augmentation of stroke volume even at the highest heart rates. The long-term effects of endurance exercise on the heart are unknown. Endurance exercise is associated with a transient increase in serum concentrations of biomarkers of cardiac damage and ventricular dysfunction which improves within 72 h. Over the past decade, there have been emerging studies reporting attenuated mortality benefit amongst individuals who perform the highest volume of exercise. Studies in lifelong male athletes aged above 40 years old show a higher prevalence of high coronary artery calcium scores (>300 Agatston units), a higher coronary plaque burden, and myocardial fibrosis compatible with subclinical myocardial infarction compared with relatively sedentary healthy controls, raising speculation that lifelong intense exercise imposes chronic coronary stress on the heart. This review article will provide a critical analysis of the existing data. Life-long middle-aged male 1 endurance athletes demonstrate increased prevalence of high coronary calcium scores. Contributing factors include genetic predisposition, ageing and the prevalence or recognised atherosclerotic risk factors. Additionally, exercise is associated with mechanical flexing of the arteries, coronary inflammation and a hypertensive response to exercise. Some athletes may develop ischaemic scar and increased risk of ventricular arrhythmias, however longitudinal studies are necessary to investigate this further. BP, blood pressure; IL1, interleukin-1; PTH, parathyroid hormone; TNFa, tumour necrosis factor alpha. Life-long middle-aged male 1 endurance athletes demonstrate increased prevalence of high coronary calcium scores. Contributing factors include genetic predisposition, ageing and the prevalence or recognised atherosclerotic risk factors. Additionally, exercise is associated with mechanical flexing of the arteries, coronary inflammation and a hypertensive response to exercise. Some athletes may develop ischaemic scar and increased risk of ventricular arrhythmias, however longitudinal studies are necessary to investigate this further. BP, blood pressure; IL1, interleukin-1; PTH, parathyroid hormone; TNFa, tumour necrosis factor alpha.